The Illocutionary Act of the First Indonesian Presidential Candidate Debate in 2024 - Renref, Jesica; Oktoviandry, Rifki (Universitas Negeri Padang, 2024)
This research investigated the types of illocutionary acts of presidential candidate in the first presidential candidate debate 2024. This research aimed at finding the types of illocutionary act as well as the intention. Descriptive qualitative method is used in this research. The data was analyzed using Austin (1962) and Searle (1976) theory. The finding revealed that there were 215 utterances of illocutionary acts in total from the 5 types, namely assertive, directive, commissive, expressive, and declarative. The candidates mostly used the assertive with informing and asserting acts. Anies Used 38 utterance of assertive, Prabowo used 23 utterances of assertive, and Ganjar used 30 utterances of assertive. The aimed of the act to establish the speaker’s credibility and demonstrate their knowledge and understanding of certain issues. Anies used informing act with the intention to get public attention and sympathy. Prabowo used asserting act with the intention to convince the public. While, Ganjar used informing and asserting act with the intention to get public attention and sympathy as well as to convince the public. Anis and Ganjar were clearer and calmer in expressing their views while Prabowo was not very clear in expressing his views, he only emphasized firmness in defending the country without stating clear actions.